Expert opinions and scientific evidence for colonoscopy key performance indicators. Issue 12 (8th October 2016) - Rees, Colin J; Bevan, Roisin; Zimmermann-Fraedrich, Katharina; Rutter, Matthew D; Rex, Douglas; Dekker, Evelien; Ponchon, Thierry; Bretthauer, Michael; Regula, Jaroslaw; Saunders, Brian; Hassan, Cesare; Bourke, Michael J; et al.
Abstract : Colonoscopy is a widely performed procedure with procedural volumes increasing annually throughout the world. Many procedures are now performed as part of colorectal cancer screening programmes. Colonoscopy should be of high quality and measures of this quality should be evidence based. New UK key performance indicators and quality assurance standards have been developed by a working group with consensus agreement on each standard reached. This paper reviews the scientific basis for each of the quality measures published in the UK standards.